2020
DOI: 10.1007/s11947-020-02546-2
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Spectroscopy in the Characterization of Bread with Turmeric Addition

Abstract: In this research, we to apply photoacoustic spectroscopy and evaluate bread added with turmeric (Curcuma longa Linnaeus) at different concentrations in relation to wheat flour weight (0, 1.25, 2.5, 5 and 10%). The amplitude of the photoacoustic signal was related to measures of antioxidant activity and evaluate the sanitary quality and also, the texture, color and sensory acceptability of the breads. It is shown that: i) The photoacoustic signal produced by bread significantly increases with the turmeric conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 102 publications
2
10
0
Order By: Relevance
“…Other studies in fortified bread have shown the relationship of photoacoustic absorption spectra with bread antioxidant activity, when added with turmeric. The found findings showed that the bread antioxidant activity is directly proportional to the concentration of turmeric powder added to bread, and to the photoacoustic signal amplitude at 515 nm ( Hernandez-Aguilar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in fortified bread have shown the relationship of photoacoustic absorption spectra with bread antioxidant activity, when added with turmeric. The found findings showed that the bread antioxidant activity is directly proportional to the concentration of turmeric powder added to bread, and to the photoacoustic signal amplitude at 515 nm ( Hernandez-Aguilar et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, it should be noted that, several spectroscopic techniques have been applied for food analysis as Raman, Nuclear magnetic resonance, Fluorescence, atomic absorption spectroscopy, Near infrared, visible/infrared, and UV/VIS ( Pojić and Mastilović, 2013 ; Karoui and Blecker, 2011 ; Pankaj et al, 2018 ). These techniques have been applied to characterize pesticides, fumonisins, differentiation of grains, coffee, oils, minerals, adulterations of wines and spices, fermentations and bioactive elements of food and plants ( Sowoidnich et al, 2010 ; Lee and Herrman, 2016 ; Pojić and Mastilović, 2013 ; Foca et al, 2011 ; Lu et al, 2011 ; Aleixandre-Tudo et al, 2017 ; Hernández et al , 2019a ; 2020a ; Bolarinwa et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bread dough was elaborated at different concentrations of TP (A, B, C, D and E) in proportion to weight of the wheat flour (600 g). Bread formulations according to Hernández et al [35] were elaborated with basic ingredients of dry yeast powder (11 g, "Tradi-Pan"), egg (48-50 g, "San Juan"), olive oil (70 g, "Oli de nutrioli"), salt (1.25 g, "Pragna"), sugar (4 g, "Zulca") and warm water (300 mL), appropriate quantity to handle the dough. The formulations expressed by percentage are possible observe in Table 1.…”
Section: Preparation Of Breadmentioning
confidence: 99%
“…In this way, when preservatives are not used, a microbial problem occurs due to fungi; the main cause of bread deterioration since it can reduce its useful life generating economic losses and consumer dissatisfaction [24,31]. The problem increases in high temperature areas [32], being the most common to develop the Mucor, Rhizopus, Aspergillus, Penicillium and Fusarium sp [24,[33][34][35]. Some of these fungi have been associated with problems of hepatotoxicity, nephrotoxicity, and hyperestrogenism since they are producers of Mycotoxins [36][37][38].…”
Section: Introductionmentioning
confidence: 99%